Data from: Horn growth variation and hunting selection of the Alpine ibex - Büntgen, Ulf; Galván, Juan Diego; Mysterud, Atle; Krusic, Paul J.; Hülsmann, Lisa; Jenny, Hannes; Senn, Josef; Bollmann, Kurt (Dryad, 2019)
Selective hunting can affect demographic characteristics and phenotypic
traits of the targeted species. Hunting systems often involve harvesting
quotas based on sex, age and/or size categories to avoid selective
pressure. However, it is difficult to assess whether such regulations
deter hunters from targeting larger “trophy” animals with longer horns
that may have evolutionary consequences. Here, we compile 44,088 annually
resolved and absolutely dated measurements of Alpine ibex (Capra ibex)
horn growth increments from 8,355 males, harvested between 1978 and 2013,
in the eastern Swiss Canton of Grisons. We aim to determine whether male
ibex with longer horns were preferentially targeted, causing animals with
early rapid horn growth to have shorter lives, and whether such hunting
selection translated into long‐term trends in horn size over the past four
decades. Results show that medium‐ to longer‐horned adult males had a
higher probability of being harvested than shorter‐horned individuals of
the same age and that regulations do affect the hunters’ behaviour.
Nevertheless, phenotypic traits such as horn length, as well as body size
and weight, remained stable over the study period. Although selective
trophy hunting still occurs, it did not cause a measurable evolutionary
response in Grisons’ Alpine ibex populations; managed and surveyed since
1978. Nevertheless, further research is needed to understand whether
phenotypic trait development is coinfluenced by other, potentially
compensatory factors that may possibly mask the effects of selective,
long‐term hunting pressure.
HornGrowthIncrementsAnnually resolved and absolutely dated measurements of
Alpine ibex (Capra ibex) horn growth increments from 8’355 males,
harvested between 1978 and 2013, in the eastern Swiss Canton of Grisons.
Keywords: Wildlife Management; Capra ibex; evolutionary change; Alpine ungulate; horn growth; 1978-2013; trophy hunting